PELATIHAN PENYUSUNAN LKPD BAHASA INDONESIA BERBASIS ETNOPEDAGOGI DI SD N 10 PEMECUTAN - I Gusti Ayu Putu Tuti Indrawati; Ida Ayu Made Wedasuwari; Ni Nyoman Ayu Tri Laksmi; Ni Luh Eka Purnami Pinatih; Mareta Dwi Setyaningrum (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
This community service was carried out because of the problems faced by teachers at SD N 10 Pemecutan related to learning tools, teachers use several learning tools such as lesson plans, learning media, learning materials and LKPD, but the use of LKPD still uses LKS which have not been made specifically by utilizing wisdom. local Bali, even though the implementation of LKPD based on local wisdom is really needed because the LKPD links and develops learning concepts with local wisdom that exists in the local area. The local wisdom values ​​contained in the LKPD can be a foundation for developing Indonesian language learning. Community service activities regarding training in preparing Indonesian language LKPD based on ethnopedagogy have been running and are 100% realized. This service was carried out by providing materials, training in preparing LKPD, and assistance in preparing LKPD in Indonesian based on ethnopedagogy. This was shown by the questionnaire average of 94.5% of teachers feeling that the training carried out was very effective